1992
DOI: 10.1002/pro.5560011108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the antigen combining site of an anti‐dinitrophenyl antibody, ANO2

Abstract: A model structure has been constructed for a monoclonal anti-dinitrophenyl antibody. The antibody, AN02, has been sequenced and cloned (Anglister, J., Frey ) was used to model the six hypervariable loops that contain the antigen-combining site. All the possible conformations of the loop backbones were constructed and the best loop structures were selected using a combination of the CHARMM potential energy function and evaluation of the solvent-accessible surface area of the conformers. The order in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…L3 has one homologous substitution (S93 VH N). CDRs with identical lengths and same critical residues assume canonical structures (Chothia and Lesk, 1987;Anchin et al, 1991;Bassolino-Klimas et al, 1992;Mas et al, 1992;Tanner et al, 1992;Orlandini et al, 1994;Tenette-Souaille and Smith, 1998;Tenette et al, 1996). Therefore the backbone conformations of CDRs L1, L2, L3, and H1 are assumed to be the same as that of the template.…”
Section: Models Of Hh8 Loops L1 L2 L3 and H1mentioning
confidence: 99%
See 1 more Smart Citation
“…L3 has one homologous substitution (S93 VH N). CDRs with identical lengths and same critical residues assume canonical structures (Chothia and Lesk, 1987;Anchin et al, 1991;Bassolino-Klimas et al, 1992;Mas et al, 1992;Tanner et al, 1992;Orlandini et al, 1994;Tenette-Souaille and Smith, 1998;Tenette et al, 1996). Therefore the backbone conformations of CDRs L1, L2, L3, and H1 are assumed to be the same as that of the template.…”
Section: Models Of Hh8 Loops L1 L2 L3 and H1mentioning
confidence: 99%
“…The sequences of thousands of antibodies of the IgG class have been determined (Kabat et al, 1991). However, the three-dimensional structures of only a small subset of sequenced antibodies have been determined by x-ray crystallography, but several have been homology-modeled (Anchin et al, 1991;Bassolino-Klimas et al, 1992;Mas et al, 1992;Tanner et al, 1992;Barry et al, 1994;Orlandini et al, 1994;Tenette-Souaille and Smith, 1998;Tenette et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Further work confirmed that in addition to the effects of the parent compounds, nitrophenylated cells and proteins were also potent immunogens [23,24] , although this was cell type and protein dependent. Antibodies generated in response to DNP-and TNPmodified proteins and peptides have been well studied and appear to be heterogenous in specificity and affinity for DNP [25][26][27] , although most react both to the modified amino acids and modified peptides.…”
Section: Nitrohalobenzenesmentioning
confidence: 99%